Functional abilities at age 4 years of children born before 29 weeks of gestation. Issue 6894 (26th June 1993) - Johnson, A; Townshend, P; Yudkin, P; Bull, D; Wilkinson, A R
Abstract : OBJECTIVES--To assess the rate of impairment and disability among babies born very preterm and to investigate the association between such impairment and gestational age at birth. DESIGN--Cohort study of a geographically defined population of babies. SETTING--Oxford Regional Health Authority. SUBJECTS--All babies born alive before 29 weeks of gestation to mothers resident in the region during 1984-6. MAIN OUTCOME MEASURES--Survival rates and rates of impairment and disability among survivors at the age of 4 years. RESULTS--Of the 342 babies, half (170) survived to be discharged home. Of the 164 survivors to age 4 years, 153 (93%) were assessed. A total of 35 (23%; 95% confidence interval 16% to 30%) were severely disabled and only 54 (35%; 28% to 43%) were unimpaired. The risk of impairment and disability increased with decreasing gestational age at birth (p < 0.003). CONCLUSIONS--With the increasing survival rate among babies born before 29 weeks of gestation, we need urgently to establish reliable ways of monitoring the proportion of survivors who have a disability.